“Strange Coupling”: Vegan Ecofeminism and Queer Ecologies in Theory and in Practice Chapter 2: Queer Ecologies, Complications and Possibilities in Coupling with Queer Vegan Ecofeminism(s) - Jiménez Rodríguez, Adriana (Revista de Lenguas Modernas, 2018)
This chapter begins by defining queer ecologies and providing a synthesis of some of the most relevant queer ecological analyses available so far while critiquing them from a vegan ecofeminist point of view. The main objective of the chapter is to prove that theoretically, it is possible to achieve a vegan ecofeminist queer ecological critical stance. The chapter also provides specific guidelines to such vegan ecofeminist queer ecological analyses.